2014
DOI: 10.1371/journal.pone.0099787
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Recovery of Visual Function after Macula-Off Rhegmatogenous Retinal Detachment

Abstract: PurposeTo determine which factors affect the recovery of visual function in macula off rhegmatogenous retinal detachment (RRD).MethodsIn a prospective study of forty-five patients with a primary macula-off RRD of 24 hours to 6 weeks duration, the height of the macular detachment was determined by ultrasonography. At 12 months postoperatively, best corrected visual acuity (BCVA), contrast acuity, and color confusion indexes (CCI) were obtained.ResultsMacular detachment was present for 2–32 (median 7) days befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
16
0
3
Order By: Relevance
“…In our study, the duration of macular detachment prior surgical intervention showed statistically significant correlation with post-operative logMAR BCVA (r=0.503, p 0.001). This result matches well with the studies done by Van de Put and colleagues [8] .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the duration of macular detachment prior surgical intervention showed statistically significant correlation with post-operative logMAR BCVA (r=0.503, p 0.001). This result matches well with the studies done by Van de Put and colleagues [8] .…”
Section: Discussionsupporting
confidence: 93%
“…The height of macular detachment was previously reported to influence visual recovery. Lower height of macular detachment correlates with better visual outcome 29,30 . This current study observed a consistent negative association between the macular detachment height and the final BCVA, but this trend was not statistically significant (regression coefficient: −0.466, p = 0.069).…”
Section: Discussionmentioning
confidence: 99%
“…Ce résultat paraît étonnant, étant donné l'urgence de la prise en charge : il faut en effet agir dans les 7 premiers jours de DDM pour obtenir les meilleurs résultats en termes d'acuité postopératoire [6][7][8][9][10], mais au-delà de 10 jours, la rapidité d'intervention ne paraît que peu influencer l'acuité finale [11,12].…”
Section: Discussionunclassified
“…On parle alors de Durée de décollement maculaire (DDM). De nombreuses études, rétrospectives, portant sur une centaine de patients chacune, amènent aux mêmes conclusions : aucune différence dans l'acuité finale postopé-ratoire n'est retrouvée si la prise en charge chirurgicale se déroule dans la première semaine de DDM [6][7][8][9][10]. Au-delà de 10 jours, le délai de prise en charge semblerait n'avoir que peu d'impact sur l'acuité finale [11,12].…”
Section: Introductionunclassified